Los profesores e investigadores universitarios de ciencias sociales y humanidades y los artículos académicos: criterios de selección y opinión - Arquero Avilés, Rosario; Salvador Oliván, José Antonio; Lamarca Langa, Genaro (Revista General de Información y Documentación, 2009)
Analysis of results of a survey sent to teachers and researchers of Humanities and Social Sciences of universities and Council for Scientific Research in Spain. There were 2398 answers. We study criteria for selecting articles for reading, their viewpoints on how to select articles for publication in journals and their views about the quality assessment of articles and journals.